Usefulness of PET/CT Imaging in Systemic IgG4-related Sclerosing Disease. A Report of Three Cases - Nguyen, Vien X; De Petris, Giovanni; Nguyen, Ba D (JOP. Journal of the Pancreas, 2011)
Autoimmune pancreatitis is the pancreatic manifestation of a novel clinicopathological disorder called systemic IgG4-related sclerosing disease. Beside the pancreas, this entity affects other sites (salivary glands, orbit, lung, thyroid, gallbladder, biliary tree system, kidney, abdominal aorta, retroperitoneum, prostate, and lymph node) by infiltration with IgG4-positive plasma cells. Several case reports and small case series have demonstrated the utility of integrated positron emission tomography/computed tomography (PET/CT) in monitoring therapy and documenting relapse and flare-up of autoimmune pancreatitis. However, there are no reports on the usefulness of PET/CT in selecting extrapancreatic sites for tissue sampling. We herein demonstrate the clinical utility of integrated PET/CT in 3 cases of systemic IgG4-related sclerosing disease for targeting extrapancreatic biopsy sites. Image: Diffuse tracer uptake by the pancreas (crosshairs).